A participatory learning approach to biochemistry using student authored and evaluated multiple‐choice questions - Bottomley, Steven; Denny, Paul (Biochemistry and molecular biology education, 2011)
A participatory learning approach, combined with both a traditional and a competitive assessment, was used to motivate students and promote a deep approach to learning biochemistry. Students were challenged to research, author, and explain their own multiple‐choice questions (MCQs). They were also required to answer, evaluate, and discuss MCQs written by their peers. The technology used to support this activity was PeerWise—a freely available, innovative web‐based system that supports students in the creation of an annotated question repository. In this case study, we describe students' contributions to, and perceptions of, the PeerWise system for a cohort of 107 second‐year biomedical science students from three degree streams studying a core biochemistry subject. Our study suggests that the students are eager participants and produce a large repository of relevant, good quality MCQs. In addition, they rate the PeerWise system highly and use higher order thinking skills while taking an active role in their learning. We also discuss potential issues and future work using PeerWise for biomedical students. Biochemistry and Molecular Biology Education Vol. 39, No. 5, pp. 352–361, 2011